Longitudinal study of computerized cardiotocography in early fetal growth restriction. (July 2017) - Wolf, H.; Arabin, B.; Lees, C. C.; Oepkes, D.; Prefumo, F.; Thilaganathan, B.; Todros, T.; Visser, G. H. A.; Bilardo, C. M.; Derks, J. B.; Diemert, A.; Duvekot, J. J.; et al.
Abstract: Objectives: To explore whether, in early fetal growth restriction (FGR), the longitudinal pattern of fetal heart rate (FHR) short‐term variation (STV) can be used to identify imminent fetal distress and whether abnormalities of FHR recordings are associated with 2‐year infant outcome. Methods: The original TRUFFLE study assessed whether, in early FGR, delivery based on ductus venosus (DV) Doppler pulsatility index (PI), in combination with safety‐net criteria of very low STV on cardiotocography (CTG) and/or recurrent FHR decelerations, could improve 2‐year infant survival without neurological impairment in comparison with delivery based on CTG monitoring only. This was a secondary analysis of women who delivered before 32 weeks and had consecutive STV data recorded > 3 days before delivery and known infant outcome at 2 years of age. Women who received corticosteroids within 3 days of delivery were excluded. Individual regression line algorithms of all STV values, except the last one before delivery, were calculated. Life tables and Cox regression analysis were used to calculate the daily risk for low STV or very low STV and/or FHR decelerations (below DV group safety‐net criteria) and to assess which parameters were associated with this risk. Furthermore, it was assessed whether STV pattern, last STV value or recurrent FHR decelerations were associated with 2‐year infant outcome. Results: One hundred and forty‐nine women from the original TRUFFLE study met the inclusion criteria. Using the individual STV regression lines, prediction of a last STV below the cut‐off used by the CTG monitoring group had sensitivity of 42% and specificity of 91%. For each day after study inclusion, the median risk for low STV (CTG group cut‐off) was 4% (interquartile range (IQR), 2–7%) and for very low STV and/or recurrent FHR decelerations (below DV group safety‐net criteria) was 5% (IQR, 4–7%). Measures of STV pattern, fetal Doppler (arterial or venous), birth‐weight multiples of the median and gestational age did not usefully improve daily risk prediction. There was no association of STV regression coefficients, a low last STV and/or recurrent FHR decelerations with short‐ or long‐term infant outcomes. Conclusion: The TRUFFLE study showed that a strategy of DV monitoring with safety‐net criteria of very low STV and/or recurrent FHR decelerations for delivery indication could increase 2‐year infant survival without neurological impairment. This post‐hoc analysis demonstrates that, in early FGR, the daily risk of abnormal CTG, as defined by the DV group safety‐net criteria, is 5%, and that prediction is not possible. This supports the rationale for CTG monitoring more often than daily in these high‐risk fetuses. Low STV and/or recurrent FHR decelerations were not associated with adverse infant outcome and it appears safe to delay intervention until such abnormalities occur, as long as DV‐PI is within normal range. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.